Reflexiòn bioètica sobre el proceso salud-enfermedad - Sánchez Morales, Margarita María; Pontificia Universidad Javeriana (2011)
Esta reflexión propone caracterizar el paradigama positivista a partir del cual se han generado las teorías biológicas de las ciencias de la salud, hacer una crítica de los obstáculos epistemológicos que han impedido  la construcción de una teoría social del proceso salud-enfermedad y presentar las propuestas no positivistas surgidas de las ciencias sociales y humanas para el desarrollo de esta teoría.ABSTRACTThe main topic in this prsentation is that humanism is part of the theoretical and scientific development of the nursing profession. To support this, I begin my exposition with an analysis of the thinking on nursing as opposed to medical thinking. Then I present a series of significant facts that have influenced the development of nursing, followed by a study of the different sorts of interrelations between discipline and profession, and their application in nursing. Subsequently, I analyze  the implications of this new thinking on nursing to finally include some reflections as conclusions.